Influence of Hypoxia and Hypercapnia on Fatty Acid Composition of Lipids in White Muscles of Common Carp Cyprinus carpio - Sysoliatin, Sergii V.; Midyk, Svitlana V.; Khyzhnyak, Svitlana V. (Problems of Cryobiology and Cryomedicine, 2017)
Study of the involvement of fish tissue fatty acids into the organism reactivity caused by an influence of exogenous factors is crucial for investigation of cell mechanisms underlying hypobiotic effect. Gas chromatography was used to estimate the composition and quantities of fatty acids of total lipids in white muscles of the Ukrainian scaly carp species. Twenty eight fatty acids were identified and their quantitative redistribution was revealed under hypoxic-hypercapnic action following a decrease in the environmental temperature (artificial hibernation). The decrease in total content of saturated and an increase in the one of unsaturated fatty acids was mainly due to the ω-3 and ω-6 polyunsaturated acids family. The optimum ω-3/ω-6 ratio under the studied conditions was supposedly maintained due to acyl-lipid ω-3 and ω-6-desaturase activity. Modified content of total lipids fatty acids in carp white muscles was likely a part of the cell mechanism of hypobiosis factors action in the fish organism. Probl Cryobiol Cryomed 2017; 27(3): 195–202